If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + 26x = 30 Solving 17 + 26x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 26x = 30 + -17 Combine like terms: 17 + -17 = 0 0 + 26x = 30 + -17 26x = 30 + -17 Combine like terms: 30 + -17 = 13 26x = 13 Divide each side by '26'. x = 0.5 Simplifying x = 0.5
| -2x^2-x-3=0 | | 14-t=-10 | | 8.26x+4=68.2276+2x | | y=-.2x+12 | | 14.95-7.55= | | 13-k=5 | | 3/4x-7/4=8 | | 14r+12r=832 | | 9x+2=27x | | 5.7(x-1)=-0.3+42.3 | | -3y-2=-2y | | -7x^3*8x^2= | | 9x^2+24x=9 | | 5m^2=112+8m | | p^2+3p^3-3p-1=0 | | 11-x+3=3n+3n | | G(t)=t+5 | | 2(v-5)+7v=4 | | 2x+8=360 | | -8n= | | 10x-6x=25-25 | | 62=9g | | 53=9g | | 44=9g | | 35=9g | | 26=9g | | 17=9g | | 4x+10(x+2)=60 | | X^2-5=3x+5 | | 8=9g | | 5y=-3x+14.50 | | 5r-1=19whatisr |